2013
DOI: 10.1682/jrrd.2013.01.0003
|View full text |Cite
|
Sign up to set email alerts
|

Transfemoral sockets with vacuum-assisted suspension comparison of hip kinematics, socket position, contact pressure, and preference: Ischial containment versus brimless

Abstract: Abstract-The objective of this study was to investigate the effect of brimless compared with ischial ramus containment (IRC) prosthetic sockets when using vacuum-assisted suspension (VAS) on persons with a unilateral transfemoral amputation (TFA). A randomized crossover design with a 2 d accommodation was used. People with unilateral TFA (n = 9 analyzed) were enrolled. Interventions were IRC VAS and brimless VAS sockets. Main outcome measures included coronal hip angle and vertical and lateral socket movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 26 publications
(42 reference statements)
4
71
0
Order By: Relevance
“…This reduces function of the prosthesis for the amputee. Although common, the SOC IRC interface design has potential limitations, such as limiting range of motion, decreasing comfort, and interfering with urogenital function, and potential fitting complications affecting overall quality of life (21,22). Benefits of a novel TFA interface such as the HiFi could potentially address areas identified as problematic and lead to alternative interface designs that improve quality of life among TFA patients.…”
Section: Discussionmentioning
confidence: 99%
“…This reduces function of the prosthesis for the amputee. Although common, the SOC IRC interface design has potential limitations, such as limiting range of motion, decreasing comfort, and interfering with urogenital function, and potential fitting complications affecting overall quality of life (21,22). Benefits of a novel TFA interface such as the HiFi could potentially address areas identified as problematic and lead to alternative interface designs that improve quality of life among TFA patients.…”
Section: Discussionmentioning
confidence: 99%
“…The current work was developed to directly test this knowledge gap. Of note, how the socket interfaces with the residual limb also affects gait [22], medial proximal skin pressure [15], comfort [15,22], and therefore possibly residual limb health. To eliminate socket interface as a confounding variable in the present study, the same socket design was used for SoC and EVS testing.…”
Section: Discussionmentioning
confidence: 99%
“…EVS sockets continue to grow in popularity on the basis of improved fit and function [5][6][7][8] through a reduction of pistoning [5,[9][10][11] and residual-limb volume management [5,[12][13]. A recent systematic review of EVS studies [14] identified only two peer-reviewed journal publication related to the effects of EVS on residual-limb physiology [5,15] and underscores the need for more evidence-based research in this underserved field. The lack of objective data on the physiological effects of EVS represents a critical barrier to develop the overall clinical significance of the socket platform on residual-limb health.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this and give the user control, the socket interface must be tightly fit and must enclose the majority of the residual limb. This can be uncomfortable, evidenced by more than 30% of lower extremity users noting problems with their socket interfaces, including skin breakdown, excessive heat and subsequent perspiration, limited range of motion, interference with urogenital function, quality of life, and function (2,3). Socket interface problems lead to more than 30 percent of amputees reducing their prosthetic use and having diminished quality of life and some choosing not to wear a prosthesis at all (4,5).…”
Section: Introductionmentioning
confidence: 99%